Pengaruh Lokasi terhadap Keputusan Pembelian Yumichi Resto Catering, Harapan Indah Bekasi - Jesica Laurensia; Sofiani Sofiani (Institut Ilmu Sosial dan Manajemen STIAMI, 2023)
Location is an important factor in increasing a business. Several studies have proven that location has an effect on purchasing decisions. This study aims to determine whether location has an effect on purchasing decisions at Yumchi Resto Catering at Kota Harapan Indah, Bekasi. The research method used is a quantitative research method, with the sample of 96 respondent of Yumchi Resto Catering’s customer. The data analysis test used was to determine the effect between the indepedent variable and the dependent variable. The results of this study are the location (X) of the purchase decision (Y) has a tcount value of 15,347 with a sig value. of 0.000 < 0.05. It shows that the location (X) has a positive and significant influence on purchasing decisions (Y). The conclusion and suggestion from this research is that location has a positive and significant influence on purchasing decisions at Yumchi Resto Catering, Harapan Indah Bekasi. It can be seen that a strategic location can determine the success of a business. Yumchi Resto Catering can continue to maintain its current location and can expand its restaurant area in order to increase customer capacity.